Case report: Managing multisystem inflammatory syndrome in children (MIS-C) in Lao People's Democratic Republic, a success story - Douangboupha, Vannida; Nhiacha, Kouyang; Sodaluck, Bounloth; Thepmixay, Daosavanh; Krohn, Kristina M. (Frontiers in Pediatrics, 2023)
Introduction: Multisystem inflammatory syndrome in children (MIS-C) is believed to be one of the most important life-threatening complications of COVID-19 infection among children. In any setting, early recognition, investigations, and management of MIS-C is crucial, but it is particularly difficult in resource-limited settings (RLS). This is the first case report of MIS-C in Lao People’s Democratic Republic (Lao PDR) that was promptly recognized, treated, and resulted in full recovery with no known complications despite the resource limitations. Case presentation: A healthy 9-year-old boy presented to a central teaching hospital fulfilling the World Health’s Organization’s MIS-C criteria. The patient had never received a COVID-19 vaccine and had a history of COVID-19 contact. The diagnosis was based upon the history, changes in the patient’s clinical status, and response to treatment and negative testing and response to treatment for alternative diagnoses. Despite management challenges relating to limited access to an intensive care bed and the high cost of IVIG; the patient received a full course of treatment and appropriate follow-up cares post discharge. There were several aspects to this case that may not hold true for other children in Lao PDR. First, the family lived in the capital city, close to the central hospitals. Second, the family was able to afford repeated visits to private clinics, and the cost of IVIG, and other treatments. Third, the physicians involved in his care promptly recognized a new diagnosis. Conclusions: MIS-C is a rare but life-threatening complication of COVID-19 infection among children. The management of MIS-C requires early recognition, investigations, and interventions which may be difficult to access, cost-prohibitive, and further increase demand on healthcare services that are already limited in RLS. Nevertheless, clinicians must consider means for improving access, determine which tests and interventions are worth the cost, and establishing local clinical guidelines for working within resource constraints while awaiting additional assistance from local and international public health systems. Additionally, using COVID-19 vaccination to prevent MIS-C and its complication for children may be cost-effective.